Simplification of sun tracking mode to gain high concentration solar energy - Omar, Aliman; Ismail, Daut; Muzamir, Isa; Mohd Rafi, Adzman (Science Publications, 2009)
Link to publisher's homepage at http://scipub.org/scipub/index.php